Subtilase from Beauveria sp.: conformational and functional investigation of unusual stability - Dalal, Sayli A.; More, Snehal V.; Shankar, Shiv; Laxman, Ryali Seeta; Gaikwad, Sushama M. (European Biophysics Journal With Biophysics Letters, 2014)
Retention of total activity of the subtilisin-like serine protease from Beauveria sp. MTCC 5184 (Bprot) in the vicinity of (1) 3 M GdnHCl for 12 h, (2) 50 % methanol and dimethyl sulfoxide each for 24 h, and (3) proteolytic enzymes (trypsin, chymotrypsin, and proteinase K) for 48 h led to expect the enzyme to be a kinetically stable protein. Also, the structure of the protein was stable at pH 2.0. Biophysical characterization and conformational transitions were monitored using steady-state and time-resolved fluorescence, FTIR, and CD spectroscopy. Single tryptophan in the protein exists as two conformers, in hydrophobic and polar environment. The secondary structure of Bprot was stable in 3 M GdnHCl as seen in far-UV CD spectra. The active fraction of Bprot obtained from size-exclusion chromatography in the presence of GdnHCl (1.0-3.0 M) eluted at reduced retention time. The peak area of inactive or denatured protein with the same retention time as that of native protein increased with increasing concentration of denaturant (1.0-4.0 M GdnHCl). However, the kinetics of GdnHCl-induced unfolding as studied from intrinsic fluorescence revealed k (unf) of native protein to be 5.407 x 10(-5) s(-1) and a half-life of 3.56 h. The enzyme is thermodynamically stable in spite of being resistant to the denaturant, which could be due to the effect of GdnHCl imparting rigidity to the active fraction and simultaneously unfolding the partially unfolded protein that exists in equilibrium with the folded active protein. Thermal and pH denaturation of Bprot exhibited interesting structural transitions.
Keywords: Beauveria; Chemical denaturation; Conformational transitions; Serine protease; Subtilase; Thermal denaturation; Thermodynamic stability

Acid stability of the kinetically stable alkaline serine protease possessing polyproline II fold - Rohamare, Sonali; Javdekar, Vaishali; Dalal, Sayli A.; Nareddy, Pavan Kumar; Swamy, Musti J.; Gaikwad, Sushama M. (Protein Journal, 2015)
The kinetically stable alkaline serine protease from Nocardiopsis sp.; NprotI, possessing polyproline II fold (PPII) was characterized for its pH stability using proteolytic assay, fluorescence and Circular Dichroism (CD) spectroscopy, and Differential Scanning Calorimetry (DSC). NprotI was found to be functionally stable when incubated at pH 1.0, even after 24 h, while after incubation at pH 10.0, drastic loss in the activity was observed. The enzyme showed enhanced activity after incubation at pH 1.0 and 3.0, at higher temperature (50-60 A degrees C). NprotI maintained the overall PPII fold in broad pH range as seen using far UV CD spectroscopy. The PPII fold of NprotI incubated at pH 1.0 remained fairly intact up to 70 A degrees C. Based on the isodichroic point and T-m values revealed by secondary structural transitions, different modes of thermal denaturation at pH 1.0, 5.0 and 10.0 were observed. DSC studies of NprotI incubated at acidic pH (pH 1.0-5.0) showed T-m values in the range of 74-76 A degrees C while significant decrease in T-m (63.8 A degrees C) was observed at pH 10.0. NprotI could be chemically denatured at pH 5.0 (stability pH) only with guanidine thiocynate. NprotI can be classified as type III protein among the three acid denatured states. Acid tolerant and thermostable NprotI can serve as a potential candidate for biotechnological applications.
Keywords: Acid stability; DSC; Kinetic stability; Polyproline fold; Protease; Thermal unfolding